Erotisme Sebagai Bentuk Dominasi Maskulin dalam Novel Adam Hawa Karya Muhidin M Dahlan - Putri, Rahmin Meilani (TRANSFORMATIKA, 2024)
Sexuality is a form of physical communication between men and women. Through sexual acts, both can show the dominant position between masculine and/or feminine. This research aims to outline issues related to the roles of men and women in terms of sexuality and identify which of the two is more dominant. The research method used is qualitative research with literature study. Primary data is obtained from the object of research, namely the novel Adam Hawa and secondary data is obtained by researchers from various sources considered relevant to this research. This research uses feminism theory with a masculine domination perspective. This study found that some of the erotic acts found allow women to be more dominant than men. But in fact, the dominance is not absolute because in reality men are still superior or dominant than women. Maia managed to conquer Idris and dominate their sexual relationship. Even with Adam, Maia successfully achieved revenge for her heartache. However, Maia's success is inseparable from the role of men, that the presence of Marfu'ah (Maia's child) is the fruit of her sexual actions with Idris (male).